Cortical functional modifications following optic neuritis. (February 2017) - Benoliel, Tal; Raz, Noa; Ben-Hur, Tamir; Levin, Netta
Background: We have recently suggested that delayed visual evoked potential (VEP) latencies in the fellow eye (FE) of optic neuritis patients reflect a cortical adaptive process, to compensate for the delayed arrival of visual information via the affected eye (AE). Objective: To define the cortical mechanism that underlies this adaptive process. Methods: Cortical activations to moving stimuli and connectivity patterns within the visual network were tested using functional magnetic resonance imaging (MRI) in 11 recovered optic neuritis patients and in 11 matched controls. Results: Reduced cortical activation in early but not in higher visual areas was seen in both eyes, compared to controls. VEP latencies in the AEs inversely correlated with activation in motion-related visual cortices. Inter-eye differences in VEP latencies inversely correlated with cortical activation following FE stimulation, throughout the visual hierarchy. Functional correlation between visual regions was more pronounced in the FE compared with the AE. Conclusion: The different correlation patterns between VEP latencies and cortical activation in the AE and FE support different pathophysiology of VEP prolongation in each eye. Similar cortical activation patterns in both eyes and the fact that stronger links between early and higher visual areas were found following FE stimulation suggest a cortical modulatory process in the FE.